TEACHERS FROM BOYSUN (TAMADDUN NURI JURNALI, 2025)
The article provides detailed information about the innovative ideas of Mulla Khudoyberdi Baysuni, his desire to combine religious and secular knowledge, the difficulties he faced on this path, as well as Mulla Do‘st Nodir Baysuni's perseverance in the path of knowledge and his position in society. The legacy of these two Baysuni mudarris is considered an important contribution to the regional enlightenment movement.